Técnicas de evaluación y su aporte en la enseñanza del aprendizaje del idioma inglés en los estudiantes de bachillerato de la Unidad Educativa Emigdio Esparza Moreno - Molina Dulcey, Mayra Alejandra (2020)
This research addresses the evaluation techniques applied by the teacher and their contribution to the learning of the English language in the students of the "Emigdio Esparza Moreno" Educational Unit, setting itself as a general objective, analyzing the incidence of the evaluation techniques applied by the teachers in learning. The development was supported by field research. The evaluation techniques and the fundamentals of collaborative learning influence the cognitive structure of the student; teachers responsible for inter and intrapersonal learning are interested in providing guidance to students to exercise the fulfillment of their academic responsibilities to improve performance; and the evaluation techniques applied by teachers in learning are valid strategies in the educational field; where their role is not that of a traditional teacher, but rather that of a mediator of the teaching-learning process, that is, they must become a true educational leader; The teacher has been prepared with the technique or instrument that he applies to his students, but this should not be very complicated so that the student can find a way or way to develop the evaluation and thus the evaluated can have the best of successes in the learning.